Implementasi Kebijakan Dan Intervensi Politik Terkait Lingkungan Hidup Dalam Pembangunan Berkelanjutan - Irwan Parlaungan Panjaitan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Sustainable development is a development paradigm that is directly related to the balance of nature or the environment, just as the paradigm of sustainable development is a concept that is accepted as a political agenda of development for all countries in the world where the relationship between economy and ecology is important in the discussion of sustainable development itself. Sustainable development is development that meets the needs of the present without compromising the ability of future generations to meet their own needs The concept of sustainable development is a necessity to reconcile economic development, quality of life, and the environment in a diverse political framework that is interrelated at the international and global levels. Thus, it can be concluded that the meaning of sustainable development cannot be separated from environmental sustainability. A sustainable environment is expected to support human life. Sustainabledevelopment that is environmentally sound is able to improve the quality of life of present and future generations. Therefore, it is necessary to review the concept of local wisdom that exists in legislation and other Regulations that hierarchically exist under it to close loopholes and fence in such a way that the claims of local wisdom remain sacred and not easily perverted casually by the detractors of commercial economic interests for a moment. On the other hand, it is necessary to be aware of political elites and stakeholders to avoid intervention and political content of decisions taken by the government in intervening in cases of environmental damage under the pretext of natural disasters which are part of the bad side of law enforcement for environmental destruction, especially in the application of Strict Liability without having to prove a mistake.